A low hydrogen content boron carbide-alumina compact and spray slurry system for making same
Patent Information
- Application Number
- CN202611269079.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对背景技术中存在的问题,本发明提供了一种低氢含量环状碳化硼-氧化铝芯块及制备用喷雾浆料体系,以解决现有环状碳化硼-氧化铝芯块采用水基喷雾造粒工艺制备过程中,为保证喷雾颗粒具有良好的成球性能和压制性能需添加较多有机粘结剂,导致浆料体系中含氢组分增加、烧结后芯块总氢含量较高,而单纯降低粘结剂添加量又易造成浆料稳定性下降、喷雾颗粒成球率降低、颗粒强度不足及压制性能变差等技术问题
[0016]本发明提供一种低氢含量环状碳化硼-氧化铝芯块用喷雾浆料体系,按质量百分比计,包括:10wt%~30wt%碳化硼粉体、65wt%~89.5wt%氧化铝粉体、0.5wt%~5wt%烧结助剂及2.6 wt%~17 wt%有机添加剂,所述喷雾浆料体系中固含量占比为40wt%~60wt%;其中,所述氧化铝粉体包括细粒径氧化铝粉体和粗粒径氧化铝粉体,所述细粒径氧化铝粉体的D50为0.5 μm~2 μm,所述粗粒径氧化铝粉体的D50为3 μm~8 μm;与现有技术相比,本发明具备以下优点:
Smart Images

Figure CN122916628A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nuclear-grade neutron-absorbing ceramic materials and their preparation technology, and particularly to a low-hydrogen-content cyclic boron carbide-alumina core and a spray slurry system for its preparation. Background Technology
[0002] Cyclic boron carbide-alumina cores are an important class of nuclear-grade neutron-absorbing ceramic materials, typically prepared using processes such as spray granulation, compression molding, and high-temperature sintering. Among these, spray granulation improves powder flowability and enhances the uniformity and consistency of compression molding, making it a crucial step in the preparation of cyclic boron carbide-alumina cores. Therefore, the composition and properties of the spray slurry system directly affect the quality of spray granulation and subsequent molding results.
[0003] Existing spray slurries typically consist of boron carbide powder, alumina powder, sintering aids, an aqueous medium, and organic binders, dispersants, and other organic additives. To ensure good rheological properties, spray atomization performance, and particle agglomeration rate, a certain amount of organic binders and other organic additives is usually added. However, these organic components introduce hydrogen into the slurry system, increasing the total hydrogen input, which is detrimental to the low hydrogen content control requirements of nuclear-grade neutron absorbers.
[0004] Currently, to reduce the hydrogen source input in the slurry system, the method of reducing the amount of organic additives is usually adopted. However, when the amount of organic binder added is reduced to a certain extent, the slurry is prone to problems such as decreased dispersion stability, reduced granulation rate of sprayed particles, insufficient particle strength and poor pressing performance, making it difficult to balance the spray granulation performance and the requirement of low hydrogen content. Summary of the Invention
[0005] To address the problems existing in the background technology, the present invention provides a low-hydrogen-content cyclic boron carbide-alumina core block and a spray slurry system for its preparation. This solves the technical problems that, in the existing water-based spray granulation process for preparing cyclic boron carbide-alumina core blocks, a large amount of organic binder needs to be added to ensure good pelletizing and pressing performance of the sprayed particles. This results in an increase in the hydrogen content of the slurry system and a high total hydrogen content in the core block after sintering. However, simply reducing the amount of binder added can easily lead to decreased slurry stability, reduced pelletizing rate of sprayed particles, insufficient particle strength, and poor pressing performance.
[0006] The specific details of the invention are as follows: In a first aspect, the present invention provides a spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks, comprising, by mass percentage: 10 wt%~30 wt% boron carbide powder, 65 wt%~89.5 wt% alumina powder, 0.5 wt%~5 wt% sintering aid, and 2.6 wt%~17 wt% organic additives, with a solid content of 40 wt%~60 wt%. The alumina powder includes fine-particle alumina powder and coarse-particle alumina powder. The D50 of the fine-particle alumina powder is 0.5 μm to 2 μm, and the D50 of the coarse-particle alumina powder is 3 μm to 8 μm.
[0007] Optionally, the mass ratio of the fine-particle-size alumina powder to the coarse-particle-size alumina powder is 95:5 to 5:95.
[0008] Optionally, the organic additives include binders, humectants, and dispersants. The adhesive is selected from at least one of polyvinyl alcohol, polyethylene glycol, and acrylic acid; The humectant is selected from ammonium polyacrylate and / or polyethylene glycol; The dispersant is selected from at least one of octylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkyl glycoside, and polyoxyethylene-polyoxypropylene block copolymer.
[0009] Optionally, the sintering aid is selected from silicon dioxide.
[0010] Optionally, the amount of the humectant added is 0.5 wt% to 5 wt%; The humectant is selected from polyethylene glycol.
[0011] Optionally, the amount of adhesive added is 2 wt% to 10 wt%; The adhesive is selected from polyvinyl alcohol.
[0012] Optionally, the amount of the dispersant added is 0.1 wt% to 2 wt%; The dispersant is selected from octylphenol polyoxyethylene ether.
[0013] Optionally, the spray slurry system is obtained in the following manner: The boron carbide powder, the alumina powder, and the sintering aid are wet-milled and mixed, and then organic additives are added. The mixture is then wet-milled and mixed again to obtain the spray slurry system.
[0014] Secondly, the present invention provides a low-hydrogen-content cyclic boron carbide-alumina core block, wherein the core block is obtained by spray granulation of the spray slurry system described in any one of claims 1-8 to form granulated powder, and the granulated powder is then subjected to cold isostatic pressing and high-temperature sintering. The flowability of the granulated powder is within 50g / 30s; The pressure used in the cold isostatic pressing is 150 MPa to 200 MPa; The high-temperature sintering temperature is 1600 ℃~1700 ℃.
[0015] Optionally, the hydrogen content of the cyclic boron carbide-alumina core is not higher than 25 ppm.
[0016] This invention provides a spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks, comprising, by mass percentage: 10wt%~30wt% boron carbide powder, 65wt%~89.5wt% alumina powder, 0.5wt%~5wt% sintering aid, and 2.6wt%~17wt% organic additives, wherein the solid content of the spray slurry system is 40wt%~60wt%; wherein the alumina powder includes fine-particle alumina powder and coarse-particle alumina powder, the D50 of the fine-particle alumina powder being 0.5 μm~2 μm, and the D50 of the coarse-particle alumina powder being 3 μm~8 μm; compared with the prior art, this invention has the following advantages: The low-hydrogen-content spray slurry system constructed in this invention adopts a composite gradation of alumina powder with different particle sizes, optimizes the powder particle packing structure, and improves the solid-phase packing efficiency of the slurry, thereby effectively reducing the slurry's demand for organic additives. While reducing the introduction of organic hydrogen sources, the slurry can maintain good dispersibility, flowability, spray pelleting rate, and particle strength, thus achieving a low-hydrogen-content slurry system.
[0017] The low-hydrogen content spray slurry system constructed in this invention takes into account low-hydrogen performance, slurry stability and spray granulation performance, and can obtain spray granulated powder with high sphericity and good flowability, providing a stable powder basis for the subsequent preparation of low-hydrogen cyclic boron carbide-alumina core blocks. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1The effect of alumina particle size distribution on the hydrogen content (average value) of cyclic boron carbide-alumina core blocks in the spray slurry system of the present invention is shown; Figure 2 This demonstrates the effect of dispersant content on the hydrogen content of cyclic boron carbide-alumina core blocks in the spray slurry system; Figure 3 The effect of humectant content on hydrogen content in cyclic boron carbide-alumina core blocks is shown. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, any product that is the same as or similar to the present invention, derived by anyone under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of the present invention.
[0021] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0022] Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of this specification.
[0023] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] Existing technologies mainly improve slurry performance by optimizing spray process parameters or adjusting the types of organic additives. Research on reducing the need for organic binders and minimizing hydrogen input to the slurry system through optimized particle size distribution is relatively limited. Furthermore, there is a lack of low-hydrogen-content spray slurry systems and their construction methods that simultaneously consider low-hydrogen-content performance, slurry rheological properties, and spray granulation performance. This invention constructs a low-hydrogen-content spray slurry system that reduces hydrogen input by optimizing alumina particle size distribution and reducing the slurry's dependence on organic additives. This system has significant engineering application value for preparing low-hydrogen-content cyclic boron carbide-alumina core blocks. The specific implementation details of this invention are described below: In a first aspect, the present invention provides a spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks, comprising, by weight percentage: 10wt%~30wt% boron carbide powder, 65wt%~89.5wt% alumina powder, 0.5wt%~5wt% sintering aid, and 2.6wt%~17wt% organic additives, with a solid content of 40wt%~60wt%. The alumina powder includes fine-particle alumina powder and coarse-particle alumina powder. The D50 of the fine-particle alumina powder is 0.5 μm to 2 μm, and the D50 of the coarse-particle alumina powder is 3 μm to 8 μm.
[0025] In specific implementation, the spray slurry system uses alumina powder with dual particle size classification; the D50 of the fine-particle-size alumina powder is 0.5 μm to 2 μm, and the D50 of the coarse-particle-size alumina powder is 3 μm to 8 μm. By constructing an alumina composite particle size distribution system, the coarse and fine alumina particles fill the gaps between each other, significantly increasing the powder bulk density and reducing the overall specific surface area. While ensuring stable spray granulation of the slurry and that the powder has the strength required for molding, the total amount of organic hydrogen source is significantly reduced. In the spray slurry system provided by this invention, the total amount of all organic additives is between 2.6 wt% and 17 wt%, limiting the upper limit of total hydrogen input to the system from the source. This solves the inherent contradiction of "poor molding with low additives and excessive hydrogen with high additives," and is suitable for the low-hydrogen requirements of nuclear-grade neutron absorber materials.
[0026] In some embodiments, the mass ratio of the fine-particle-size alumina powder to the coarse-particle-size alumina powder is 95:5 to 5:95.
[0027] This implementation plan limits the mass ratio of fine to coarse alumina to 95:5 to 5:95. Within this range, fine particles can embed into the gaps between coarse particles to form a dense packing structure, keeping the specific surface area of the powder at a low level and maintaining a consistently low adsorption requirement for organic additives. Under actual working conditions, the ratio of coarse to fine powder can be flexibly adjusted according to the proportion of boron carbide powder and the operating conditions of the spraying equipment to maintain the optimal dense packing structure of the spray slurry system, stably achieving the technical goals of reducing the amount of organic additives and reducing hydrogen residue, while ensuring high packing density and flowability of the granulated powder.
[0028] In some embodiments, the organic additives include binders, humectants, and dispersants. The adhesive is selected from at least one of polyvinyl alcohol, polyethylene glycol, and acrylic acid; The humectant is selected from ammonium polyacrylate and / or polyethylene glycol; The dispersant is selected from at least one of octylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkyl glycoside, and polyoxyethylene-polyoxypropylene block copolymer.
[0029] In specific implementation, among the organic additives used in this scheme, the binder is used to impart plasticity and green strength to the sprayed particles, the humectant is used to improve the plasticity of the powder and the rheology of the slurry, and the dispersant is used to eliminate the agglomeration of inorganic powders. All the organic additives used in this scheme are water-soluble organic substances that are suitable for water-based ceramic slurries, avoiding additives containing a large number of stable aromatic rings, which are difficult to decompose at high temperatures and have extremely high hydrogen residues.
[0030] In some embodiments, the sintering aid is selected from silicon dioxide. At a sintering temperature of 1600℃~1700℃, silicon dioxide can react with alumina to form a low-melting-point aluminosilicate liquid phase. This liquid phase, through capillary action, drives particle rearrangement and fills the pores of the green body, achieving low-temperature densification sintering. Furthermore, silicon dioxide is an inorganic oxide, containing no hydrogen, and will not introduce an additional hydrogen source into the system, thus not compromising the low-hydrogen index. This approach can ensure high density, excellent mechanical and neutron absorption properties of the core while completely avoiding the risk of hydrogen impurity introduction from the sintering aid, thus balancing the dual requirements of sintering densification and low hydrogen content, and is compatible with the high-purity, low-impurity control standards for nuclear materials.
[0031] In actual working conditions, the addition amount can be controlled according to the differences in hydrogen residue contribution of different additives. Humectants with thorough high-temperature decomposition and low hydrogen residue are preferred to share the lubrication requirements, such as polyethylene glycol, with an addition amount of 0.5 wt%~5 wt%. Polyethylene glycol has a short-chain aliphatic ether structure and no aromatic rigid ring. It can be completely decomposed into water and carbon dioxide in the later spray granulation and high-temperature sintering stages. After sintering, there is almost no hydrogen residue, which is a low-hydrogen-contributing organic component. A relatively low addition amount can give full play to the lubrication, plasticization and humidification effects, reduce the internal friction of the slurry, improve the sphericity and flowability of the granulated powder, and small fluctuations in the addition amount of polyethylene glycol will not cause a significant increase in the hydrogen content of the core. It is a functional additive that can be flexibly controlled in the low-hydrogen slurry system and alleviate the hydrogen source pressure of the binder.
[0032] In practical applications, polyvinyl alcohol (PVA) is the preferred binder. PVA has no aromatic rings, and its hydrogen residue is significantly lower than that of phenolic polymeric dispersants at the same bonding strength, achieving a balance between molding performance and low hydrogen content. The addition amount is 2 wt% to 10 wt%. Octylphenol polyoxyethylene ether (OXE) is the preferred dispersant, and a small amount (0.1 wt% to 2 wt%) is sufficient to achieve uniform dispersion of the slurry. Utilizing alumina powder with dual-size graded composite composition, the spray slurry system effectively reduces the amount of high-hydrogen dispersants and binders while ensuring the mechanical strength, high bulk density, and flowability of the granulated powder.
[0033] In some embodiments, the spray slurry system is obtained by: The boron carbide powder, the alumina powder, and the sintering aid are wet-milled and mixed, and then organic additives are added. The mixture is then wet-milled and mixed again to obtain the spray slurry system.
[0034] In a second aspect, the present invention provides a low-hydrogen-content cyclic boron carbide-alumina core block, wherein the core block is obtained by spray granulation of the spray slurry system described in the first aspect to form granulated powder, and the granulated powder is then subjected to cold isostatic pressing and high-temperature sintering. The flowability of the granulated powder is within 50g / 30s; The pressure used in the cold isostatic pressing is 150 MPa to 200 MPa; The high-temperature sintering temperature is 1600 ℃~1700 ℃.
[0035] In some embodiments, the hydrogen content of the cyclic boron carbide-alumina core is not higher than 25 ppm.
[0036] To enable those skilled in the art to more clearly understand the present invention, the following embodiments will be used to provide a detailed description of the low-hydrogen-content cyclic boron carbide-alumina core block and the spray slurry system for its preparation.
[0037] Example 1 According to the component ratio, boron carbide powder, first alumina powder (A) with D50=1µm and second alumina powder (B) with D50=3µm (where A:B mass ratio = 50wt%:50wt%), and silica powder were added to a ball mill jar (14.5wt% boron carbide, 83.5wt% alumina, 2wt% silica powder). Deionized water was then added for wet milling to ensure uniform dispersion of the components. Subsequently, 0.5wt% dispersant octylphenol polyoxyethylene ether (TRITON X-405), 0.25wt% humectant polyethylene glycol (PEG200), and 1wt% binder polyvinyl alcohol (PVA) were added, and ball milling continued to obtain a uniformly dispersed slurry system (solid content of 48%). The ball-milled slurry was then spray-granulated at an inlet temperature of 250℃, an outlet temperature of 130℃, and an atomizer speed of 180 Hz. The obtained spray-granulated powder had a flow rate of 27 s per 50 g of powder and a bulk density of 1.62 g / cm³. 3 The high-flowability spray-granulated powder was then loaded into a cylindrical mold and cold isostatically pressed at 160 MPa. The core block was then sintered at 1660 °C for 3 h to obtain a core block with a density of 65%~68%. The core block was then machined on a centerless grinder, cleaned in an ultrasonic cleaner for 5 min, dried at 120 °C for 12 h, and further vacuum dried at 950 °C for 1 h.
[0038] The hydrogen content of the prepared annular boron carbide-alumina core was determined by the inert gas melting thermal conductivity method, and the average hydrogen content was found to be 17.38 ppm (see...). Figure 1 ).
[0039] Example 2 The difference from Example 1 is that in this example, the mass ratio of the first alumina powder (A) with D50=1um and the second alumina powder (B) with D50=3um is 70 wt%: 30 wt%, while the rest of the preparation process and parameters remain unchanged. The powder obtained by spray granulation has a flow rate of 39 s per 50 g of powder and a bulk density of 1.65 g / cm³. 3 .
[0040] The hydrogen content of the prepared annular boron carbide-alumina core was determined by the inert gas melting thermal conductivity method, and the average hydrogen content was found to be 18.06 ppm (see...). Figure 1 ).
[0041] Example 3 The difference from Example 1 is that in this example, the mass ratio of the first alumina powder (A) with D50=1um and the second alumina powder (B) with D50=3um is 90 wt%: 10 wt%, while the rest of the preparation process and parameters remain unchanged. The powder obtained by spray granulation has a flow rate of 32 s per 50 g of powder and a bulk density of 1.58 g / cm³. 3 .
[0042] The hydrogen content of the prepared annular boron carbide-alumina core was measured to be 20.94 ppm using the inert gas melting thermal conductivity method (see [link to relevant documentation]). Figure 1 ).
[0043] Example 4 The difference from Example 1 is that in this example, the mass ratio of the first alumina powder (A) with D50=1um and the second alumina powder (B) with D50=3um is 0 wt%: 100 wt%, while the rest of the preparation process and parameters remain unchanged. The powder obtained by spray granulation has a flow rate of 20 s per 50 g of powder and a bulk density of 1.53 g / cm³. 3 .
[0044] The hydrogen content of the prepared annular boron carbide-alumina core was determined by the inert gas melting thermal conductivity method, and the average hydrogen content was found to be 22 ppm (see...). Figure 1 ).
[0045] Figure 1 The effect of alumina particle size distribution on the hydrogen content (average value) of cyclic boron carbide-alumina core blocks in the spray slurry system of the present invention is shown, such as... Figure 1As shown in Examples 1-4, the correlation curves between the addition ratio of fine-particle-size alumina and coarse-particle-size alumina and the hydrogen content of the core block were obtained by changing these ratios. The horizontal axis represents the proportion of coarse-particle-size alumina (D50=3 μm) in the total alumina powder, and the vertical axis represents the hydrogen content (ppm) of the sintered core block. The red line represents the average hydrogen content under the same ratio, and the black dots represent parallel test data. The amounts of binder, dispersant, and humectant were kept constant throughout the experiment, and only the ratio of coarse to fine alumina was changed to examine the hydrogen control effect of particle size distribution. The trend shows that when the proportion of coarse-particle-size alumina gradually increases to the 50% range, the hydrogen content of the core block continues to decrease, reaching the lowest hydrogen content range in the 30%~50% coarse-particle-size alumina range, with the optimal sample having a hydrogen content as low as 17.38 ppm. When the proportion of coarse-particle-size alumina exceeds 50% and continues to increase to 100%, the hydrogen content of the core block rises again. This indicates that single fine alumina powder has a large specific surface area and numerous adsorption sites on its particle surface. In the slurry system, a large amount of organic binders and dispersants adhere to the powder surface, resulting in a high total input of organic hydrogen sources and a large residual hydrogen content after sintering. When coarse and fine alumina are combined, the fine particles fill the gaps between the coarse particles, forming a dense packing structure. This significantly reduces the overall specific surface area of the powder, significantly decreasing the powder's adsorption requirement for organic additives. With the same total amount of organic additives, less ineffective organic components are adsorbed, reducing the introduction of hydrogen impurities at the source. If the proportion of coarse alumina is too high, the filling amount of fine powder is insufficient, the interparticle gaps widen again, the specific surface area of the powder rebounds, and the hydrogen content increases simultaneously. This confirms that the combination of dual-size alumina can reduce the hydrogen content of the core at the solid-phase powder structure level, solving the problem of traditional single fine alumina powder requiring large amounts of organic additives and resulting in excessive hydrogen content in the finished product.
[0046] Example 5 The difference from Example 1 is that in this example, the mass ratio of the first alumina powder (A) with D50=1 μm and the second alumina powder (B) with D50=3 μm is 100 wt%: 0 wt%, while the rest of the preparation process and parameters remain unchanged. The powder obtained by spray granulation has a flow rate of 35 s per 50 g of powder and a bulk density of 1.32 g / cm³. 3 .
[0047] The hydrogen content of the prepared annular boron carbide-alumina core was determined by the inert gas melting thermal conductivity method, and the average hydrogen content was found to be 27.14 ppm (see...). Figure 2 ).
[0048] Example 6 The difference from Example 5 is that the content of dispersant TRITON X-405 used in this example is 2 wt%, while the rest of the preparation process and parameters remain unchanged; The obtained spray-granulated powder had a flow rate of 33 s per 50 g of powder and a bulk density of 1.36 g / cm³. 3 The hydrogen content of the prepared annular boron carbide-alumina core was measured to be 31.95 ppm using the inert gas melting thermal conductivity method (see...). Figure 2 ).
[0049] Example 7 The difference from Example 5 is that the content of dispersant TRITON X-405 used in this example is 1 wt%, while the rest of the preparation process and parameters remain unchanged; The obtained spray-granulated powder had a flow rate of 38 s per 50 g of powder and a bulk density of 1.34 g / cm³. 3 The core block was then subjected to high-temperature sintering and vacuum drying (the preparation process was consistent with that in Example 5). The hydrogen content of the prepared annular boron carbide-alumina core was determined by the inert gas melting thermal conductivity method, and the average hydrogen content was found to be 30.10 ppm (see...). Figure 2 ).
[0050] Figure 2 This study demonstrates the effect of dispersant content in the spray slurry system on the hydrogen content of cyclic boron carbide-alumina core blocks. Because TRITON X-405 molecules possess a rigid octyl aromatic phenol ring, the aromatic carbon skeleton is difficult to completely decompose during the entire process of spray drying, medium-temperature degreasing, and high-temperature sintering, leaving stable hydrocarbon groups inside the ceramic matrix. This makes it the organic component contributing the most to hydrogen residue in the entire slurry system. Examples 5-7 uniformly used gradeless pure fine alumina powder, fixed the amounts of PVA binder and PEG humectant, and only gradually adjusted the amount of dispersant TRITON X-405 to individually verify the contribution of high-hydrogen dispersant to hydrogen residue. Figure 2 As shown, the horizontal axis represents the mass fraction of dispersant added, and the vertical axis corresponds to the hydrogen content of the finished chip. The data show a clear positive correlation. When TRITON X-405 dispersant is added at 0.5 wt%, the hydrogen content of the chip is about 27.14 ppm. When the amount added is increased to 1 wt%, the hydrogen content increases to 30.10 ppm. When the amount added is increased to 2 wt%, the hydrogen content reaches 31.95 ppm. The higher the amount of dispersant, the more significant the hydrogen residue after sintering.
[0051] Further comparing Examples 1 and 5, both used 0.5 wt% of the dispersant octylphenol polyoxyethylene ether (TRITON X-405). The difference lies in that Example 5 used a single fine alumina powder, while Example 1 used a coarse-fine alumina gradation design. The single fine alumina powder in Example 5 has a large specific surface area and a large number of active adsorption sites on the powder surface. Under the same amount of organic additives, more PVA and TRITON X-405 polymers will be firmly adsorbed on the particle surface. These organic components that are difficult to decompose completely are prone to leaving hydrocarbon impurities after sintering, ultimately increasing the total hydrogen content of the finished product. Example 1 reduces the overall specific surface area of the powder by using a coarse-fine alumina gradation, which greatly reduces the adsorption requirements of the powder for organic binders and dispersants. Under the same organic addition ratio, the proportion of free and easily thermally decomposed organic components in the system increases, and hydrogen impurities can be fully removed during degreasing and sintering, reducing hydrogen residue from the source.
[0052] Example 8 The difference from Example 5 is that the content of the humectant PEG200 used in this example is increased from 0.25 wt% to 1 wt%, while the rest of the preparation process and parameters remain unchanged; The average hydrogen content of the obtained chips was 29.87 ppm (see...). Figure 3 It is evident that the humectant PEG200 did not have a significant impact on the hydrogen content of the core.
[0053] Figure 3 The effect of humectant content in the spray slurry system on the hydrogen content of cyclic boron carbide-alumina core blocks is shown, such as... Figure 3 As shown, with the dispersant fixed at a high addition of 2wt%, only the amount of PEG humectant was adjusted to compare the hydrogen residue characteristics of low-hydrogen additives. The horizontal axis represents the numbers of three parallel replicate samples. Gray squares represent the addition of 0.25wt% PEG200, and red dots represent the increase of PEG200 to 1wt%. In the three parallel samples, the hydrogen content values of the core blocks corresponding to 0.25wt% and 1wt% PEG under the same number highly overlapped, with no obvious upward trend. The data difference is only due to the random experimental error of parallel testing. Increasing the PEG addition by 4 times will hardly cause an increase in the hydrogen content of the finished product.
[0054] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0055] For the sake of simplicity, the method embodiments are described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and components involved are not necessarily essential to the present invention.
[0056] The above provides a detailed description of the low-hydrogen-content cyclic boron carbide-alumina core block and the spray slurry system for its preparation provided by the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only intended to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks, characterized in that, The spray slurry system comprises, by weight percentage: 10 wt%~30 wt% boron carbide powder, 65 wt%~89.5 wt% alumina powder, 0.5 wt%~5 wt% sintering aid, and 2.6 wt%~17 wt% organic additives, wherein the solid content of the spray slurry system is 40 wt%~60 wt%. The alumina powder includes fine-particle alumina powder and coarse-particle alumina powder. The D50 of the fine-particle alumina powder is 0.5 μm to 2 μm, and the D50 of the coarse-particle alumina powder is 3 μm to 8 μm.
2. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 1, characterized in that, The mass ratio of fine-particle-size alumina powder to coarse-particle-size alumina powder is 95:5 to 5:
95.
3. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 1, characterized in that, The organic additives include binders, humectants, and dispersants. The adhesive is selected from at least one of polyvinyl alcohol, polyethylene glycol, and acrylic acid; The humectant is selected from ammonium polyacrylate and / or polyethylene glycol; The dispersant is selected from at least one of octylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkyl glycoside, and polyoxyethylene-polyoxypropylene block copolymer.
4. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 1, characterized in that, The sintering aid is selected from silicon dioxide.
5. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 3, characterized in that, The amount of the humectant added is 0.5 wt% to 5 wt%; The humectant is selected from polyethylene glycol.
6. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 3, characterized in that, The amount of adhesive added is 2 wt% to 10 wt%; The adhesive is selected from polyvinyl alcohol.
7. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 3, characterized in that, The amount of the dispersant added is 0.1 wt% to 2 wt%; The dispersant is selected from octylphenol polyoxyethylene ether.
8. The spray slurry system for low-hydrogen-content cyclic boron carbide-alumina core blocks according to claim 1, characterized in that, The spray slurry system is obtained through the following methods: The boron carbide powder, the alumina powder, and the sintering aid are wet-milled and mixed, and then organic additives are added. The mixture is then wet-milled and mixed again to obtain the spray slurry system.
9. A low-hydrogen-content cyclic boron carbide-alumina core, characterized in that, The core block is obtained by spray granulation of the spray slurry system described in any one of claims 1-8 to form granulated powder, and then the granulated powder is subjected to cold isostatic pressing and high-temperature sintering. The flowability of the granulated powder is within 50g / 30s; The pressure used in the cold isostatic pressing is 150 MPa to 200 MPa; The high-temperature sintering temperature is 1600 ℃~1700 ℃.
10. The low-hydrogen-content cyclic boron carbide-alumina core block according to claim 9, characterized in that, The hydrogen content of the cyclic boron carbide-alumina core is not higher than 25 ppm.